2005
DOI: 10.1111/j.1467-8551.2005.00456.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance Perceptions of Organizational Citizenship Behaviours at Work: a Bi‐Level Study among Managers and Employees

Abstract: Organizational citizenship behaviours (OCB) are ‘extra‐role’, work‐directed actions theorized to contribute to organizational effectiveness. However, the link between OCB and performance is not firmly based on empirical study. First, we argue that managers and employees may have different perceptions of OCB. The level of OCB will be perceived to be higher by managers than by employees. Second, we suggest that ‘best’ performing employees will have higher levels of OCB, and a stronger OCB–performance linkage tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
87
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(93 citation statements)
references
References 54 publications
2
87
0
2
Order By: Relevance
“…In the context of research evidence that shows that managers are primarily rewarded for the results of their work, rather than for any concern shown to their employees, they argued that it was not surprising that managers tend to focus on their own short-term best interests when making decisions about the implementation of the organisation's flexible working policies. More recently, and in keeping with differences in attitudes between managers and employees, Turnipseed and Rassuli (2005) found that managers place more emphasis on measured performance whilst 'helping others in the workplace' is seen as a significant contributor to performance by employees.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of research evidence that shows that managers are primarily rewarded for the results of their work, rather than for any concern shown to their employees, they argued that it was not surprising that managers tend to focus on their own short-term best interests when making decisions about the implementation of the organisation's flexible working policies. More recently, and in keeping with differences in attitudes between managers and employees, Turnipseed and Rassuli (2005) found that managers place more emphasis on measured performance whilst 'helping others in the workplace' is seen as a significant contributor to performance by employees.…”
Section: Introductionmentioning
confidence: 99%
“…Morrison (1996) asserted that PE motivates individuals and increases their OCBs. Studies indicate that one of the indicators of JP is OCB (Posdakoff & MacKenzie, 1994;Turnipseed & Rassuli, 2005). Many researchers studied POS and PE as anterior variables of OCB (Wayne et al, 1997(Wayne et al, , 2002Yen et al, 2004).…”
Section: The Relations Between Pos Pe Ocb Je and Jpmentioning
confidence: 99%
“…Many researchers studied POS and PE as anterior variables of OCB (Wayne et al, 1997(Wayne et al, , 2002Yen et al, 2004). Job performance can be increased by OCB (Turnipseed & Rassuli, 2005). POS, OCB, and PE are closely related with JP (Niehoff et al, 2001;Chow, Lo, Sha & Hong, 2006).…”
Section: The Relations Between Pos Pe Ocb Je and Jpmentioning
confidence: 99%
See 1 more Smart Citation
“…This out-of-role performance -behavior that is not captured in reward systems-is usually referred to as 'organizational citizenship behavior' (Bolino 1999;Organ 1988a;Turnipseed & Rassuli 2005). In the traditional bureaucracy template, people execute their assigned task and more-or-less blindly rely on rules and procedures for their organization to function properly.…”
Section: Limited Influence On Resultsmentioning
confidence: 99%